2007
DOI: 10.1007/s11423-007-9058-1
|View full text |Cite
|
Sign up to set email alerts
|

Learner preferences and prior knowledge in learner-controlled computer-based instruction

Abstract: This study examined the effects of prior knowledge, learner preference for control, and type of control (learner or program) on the achievement of middle-school students in a computer-based instructional program on adding and subtracting integers. Students were blocked by preference-for-control scores and randomly assigned to either a learner-control or program-control version of instruction. A significant three-way interaction (prior knowledge · preference scores · type of control) revealed that students with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 34 publications
(65 reference statements)
2
29
0
Order By: Relevance
“…Ten items adapted from Copcha and Sullivan (2008) were used to measure control perceptions during week 8 (e.g., "In this class, I could decide how much time to spend practicing problems" and "In this class, I could decide in which order to study different chapters"), rated on a scale from 1 ¼ strongly disagree to 6 ¼ strongly agree. The items reflect learners' autonomy perceptions of how, when and in which order they complete coursework (Cronbach's alpha ¼ .92).…”
Section: Methodsmentioning
confidence: 99%
“…Ten items adapted from Copcha and Sullivan (2008) were used to measure control perceptions during week 8 (e.g., "In this class, I could decide how much time to spend practicing problems" and "In this class, I could decide in which order to study different chapters"), rated on a scale from 1 ¼ strongly disagree to 6 ¼ strongly agree. The items reflect learners' autonomy perceptions of how, when and in which order they complete coursework (Cronbach's alpha ¼ .92).…”
Section: Methodsmentioning
confidence: 99%
“…Rieber (1990) found that students learning Newton's Laws of Physics scored higher on tests after using an interactive animation (an animation followed by multiple-choice questions including feedback). In addition, Kopcha and Sullivan (2008) have found that high-prior-knowledge students achieved better when their preference for interactivity was matched with the type of program they used. There is one assumption underlying all of these interactivity theories: the higher the interactive level, the better the product.…”
Section: Proactive Interactionmentioning
confidence: 99%
“…With regard to learning, learners may not develop motives for choosing between tasks that differ in their structural features and thus be unable to distinguish between tasks that are necessary for learning and tasks that could just as well be omitted (Ross & Morrison, 1989). This negatively influences the learning process (Kopcha & Sullivan, 2008;Tennyson & Buttery, 1980;Williams, 1996) and even enlarges individual differences between low and high ability learners (Merrill, 2002;Snow, 1980). With regard to motivation, learners who are not aware of structural differences between tasks will probably not see the reason for choosing between these tasks.…”
Section: Structural Task Featuresmentioning
confidence: 99%